Electrochromism of the Langmuir-Blodgett films based on monophthalocyanines carrying redox active metal centers - Arican, Duygu; Erdogmus, Ali; Koca, Atif (ELSEVIER SCIENCE SA, 2014)
In this study, electrochromic properties of metallophthalocyanine (MPc)-based thin films were investigated in detail with electrochemical, in situ spectroelectrochemical and in situ electrocolorimetric analysis methods. Electrochemical and spectroelectrochemical measurements of monophthalocyanines exhibited that incorporation of redox active metal centers, Co-II, (FeOAc)-O-III, and (MnOAc)-O-III, into the phthalocyanine center increases the redox richness of the complex due to the reversible metal-based reduction and oxidation couples of the metal centers. Metal based redox processes of the complexes affect the optical changes more than the Pc based redox process due to the shifting of the existence bands and appearance of new bands in the UV-vis spectrum. Optical changes especially in the visible part of the light spectrum are desired properties for usage of a material in the display technologies. Electrochromic measurements indicate that film formation methods, electrolytes, and nature of the metal ions in the phthalocyanine cavity alter the basic electrochromic parameters of the complexes. Langmuir-Blodgett films of manganese, cobalt, and iron phthalocyanines are found as ideal neutral and anodic coloring electrochromic materials due to their short color change times, long-term stability, and long-term write-erase efficiency. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; Spectroelectrochemistry; Electrochromism; Monophthalocyanine; Cobalt; Manganese; Iron; SPECTROELECTROCHEMICAL CHARACTERIZATION; PHTHALOCYANINES SYNTHESIS; THIN-FILMS; PORPHYRINS; Materials Science; Physics